Content and Context Analysis Implementation Of The Mandalika Special Economic Zone Policy: Socio-Financial and Accounting Practice Perspective - Raziqin, Khairur; Suryono, Agus; Domai, Tjahjanulin (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the implementation of the Special Economic Zone (SEZ) policy in Mandalika with a focus on policy content, implementation context, and its impacts, utilizing Grindle's policy implementation theory (1980). The findings indicate that the Mandalika SEZ has broad objectives to enhance the regional economy through tourism development. While it aims to increase tourist arrivals and create job opportunities, its implementation faces challenges such as land disputes, community participation, and infrastructure development. Nevertheless, the policy has yielded positive impacts such as local economic growth and increased tourist visits, albeit not uniformly experienced by all residents. The research methodology employed a qualitative descriptive approach with data collected through purposive sampling, including observation, interviews, and document analysis. Data analysis utilized Miles and Huberman's method to identify patterns and key findings.